2018
DOI: 10.1093/femsec/fiy141
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulfate- and hydrogen-driven autotrophic denitrification by a microbial consortium enriched from groundwater of an oligotrophic limestone aquifer

Abstract: Despite its potentially high relevance for nitrate removal in freshwater environments limited in organic carbon, chemolithoautotrophic denitrification has rarely been studied in oligotrophic groundwater. Using thiosulfate and H2 as electron donors, we established a chemolithoautotrophic enrichment culture from groundwater of a carbonate-rock aquifer to get more insight into the metabolic repertoire, substrate turnover, and transcriptional activity of subsurface denitrifying consortia. The enriched consortium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 82 publications
4
40
0
Order By: Relevance
“…A high importance of biofilm-associated microbial activity has already previously been proposed in a study investigating 12 alpine karst aquifers (including also LKAS2), revealing pronouncedly higher heterotrophic prokaryotic production rates in sediments when compared to the bacteria suspended in the water column (Wilhartitz et al, 2009). In this context, an increasing number of studies is challenging the traditional view of subsurface environments’ dependency on surface-derived, allochthonous carbon inputs, but rather suggest a high importance of chemolithoautotrophic metabolic processes such as the utilization of reduced sulfur and nitrogen compounds as energy sources as recently shown for a shallow fractured carbonte-rock model aquifer in central Germany (Herrmann et al, 2015, 2017; Kumar et al, 2017, 2018; Starke et al, 2017). Correspondingly, also a recent study on bacterial biofilm-formations attached to the stream bed of a dinaric karst cave in Slovenia reported a high abundance of bacteria affiliated to the phylum Nitrospirae , well known for their chemolithoautotrophic lifestyle (Kostanjšek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high importance of biofilm-associated microbial activity has already previously been proposed in a study investigating 12 alpine karst aquifers (including also LKAS2), revealing pronouncedly higher heterotrophic prokaryotic production rates in sediments when compared to the bacteria suspended in the water column (Wilhartitz et al, 2009). In this context, an increasing number of studies is challenging the traditional view of subsurface environments’ dependency on surface-derived, allochthonous carbon inputs, but rather suggest a high importance of chemolithoautotrophic metabolic processes such as the utilization of reduced sulfur and nitrogen compounds as energy sources as recently shown for a shallow fractured carbonte-rock model aquifer in central Germany (Herrmann et al, 2015, 2017; Kumar et al, 2017, 2018; Starke et al, 2017). Correspondingly, also a recent study on bacterial biofilm-formations attached to the stream bed of a dinaric karst cave in Slovenia reported a high abundance of bacteria affiliated to the phylum Nitrospirae , well known for their chemolithoautotrophic lifestyle (Kostanjšek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for the phreatic (i.e., water-saturated) zone of alpine karst aquifers, while considerably more studies are available on the microbiology of the vadose , unsaturated zone of karstic systems, including stagnant rock-pools, caves and epigenic cave streams (Shabarova and Pernthaler, 2010; Kostanjšek et al, 2013; Shabarova et al, 2013, 2014; Brannen-Donnelly and Engel, 2015; Wu et al, 2015; Pleše et al, 2016; Tomczyk-Żak and Zielenkiewicz, 2016). For a lowland limestone aquifer in central Germany, very recent studies demonstrated a high potential for chemolithoautotrophic metabolic processes, including denitrification linked to the oxidation of reduced sulfur compounds as well as the capacity for anaerobic ammonium oxidation (Opitz et al, 2014; Herrmann et al, 2015, 2017; Kumar et al, 2017, 2018; Starke et al, 2017). A high potential for chemolithoautotrophic processes has also been suggested based on a strong contribution of dissolved inorganic carbon to the build-up of groundwater microbial biomass (Nowak et al, 2017; Schwab et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of S. hydrogenivorans to convert arsenic had never been examined. We grew the strain under different conditions were As V was the electron acceptor or As III the electron donor, in presence or absence of thiosulfate and/or hydrogen [67]. Only As V could be converted to As III (even without thiosulfate) but not the reverse ( Figure 5A).…”
Section: Arsenic Redox Conversions By S Hydrogenivoransmentioning
confidence: 99%
“…The amplicon sequencing was performed on Illumina's MiSeq platform using v3 chemistry (Illumina, Eindhoven, Netherlands). The detailed amplicon library preparation procedures were described by Kumar et al (2018). The sequence data was analyzed using mothur V.1.39.5 (Schloss et al, 2009) according to the MiSeq SOP by Kozich et al (2013).…”
Section: Bacterial Community Analysismentioning
confidence: 99%